Effect of the Addition of Straw Fiber on the Bending Strength of Concrete Fc’ 25 - Suanto, Pengki (Syntax Corporation, 2025)
Analysis of how adding straw fibres affects concrete's mechanical qualities, namely its flexural and compressive strengths. Compressive, flexural, and slump tests were used to evaluate concrete with different percentages of straw fibres (0%, 2.5%, 5%, 7.5%, and 10%). The slump test results demonstrated that adding straw fibre decreased the concrete's workability, with the slump value falling as the percentage of straw fibre rose. Concrete testing with straw fibre revealed a considerable drop in compressive strength, going from 28 MPa in concrete without straw fibre to 20 MPa in a mixture containing 10% straw fibre. This decline results from unevenly dispersed straw fibres, which lowers the density of the concrete. But when adding straw fibre, the concrete's bending strength rose dramatically. It went from 6 MPa in concrete without straw fibre to 11 MPa in a combination containing 10% straw fibre. The study's findings indicate that straw fibres can lower concrete's compressive strength and boost the material's resistance to bending stresses. Straw fibre is an economical and environmentally beneficial additive with advantages in applications requiring strong flexural resistance. It can also lessen environmental effects.